Clinical research, mechanisms, and prospects of flavonoids from Herba Patriniae in the treatment of colorectal cancer - Zhang, PingPing; Jia, Ru; Wang, Yao; Tang, YuFei; Li, Qi; Hou, FengGang (Frontiers in Pharmacology, 2025)
Colorectal cancer (CRC) is a common and aggressive malignancy of the gastrointestinal tract with a severe disease burden. The role of Traditional Chinese Medicine (TCM) and its natural active ingredients in enhancing the therapeutic effects of radiotherapy and chemotherapy and preventing the recurrence and metastasis of CRC has been increasingly recognized. Herba Patriniae has shown significant clinical efficacy for the treatment of CRC. Flavonoids has been found to be one of the main active anticancer components of Herba Patriniae. This review summarizes the latest findings from clinical trials and in vitro studies on anticancer mechanisms of Herba Patriniae, and discusses the role of the flavonoids in combination therapy against CRC. These flavonoids exert anticancer effects through diverse mechanisms. For instance, they prevent the development of precancerous lesions, regulate the cell cycle, modulate CRC cell proliferation, promote tumor cell apoptosis, inhibite epithelial-mesenchymal transition, reverse drug resistance, and modulate gut microbiota by acting on several key signaling pathways, such as PI3K/Akt/mTOR, Wnt/β-catenin, and EGFR/ERK/MAPK. Future research should prioritize clarifying the specific dosage and safety of flavonoids under different pathological conditions, further conducting large-scale, rigorously designed clinical studies to determine the efficacy differences of flavonoids for patients with different pathological types of CRC and simultaneously delving into the mechanisms of their anti-colorectal cancer effects, as well as their interactions with the intestinal microbiota and tumor microenvironment.